Infrastructuring Urban Futures The Politics of Remaking Cities - Wiig, Alan; Ward, Kevin; Enright, Theresa; Hodson, Mike; Pearsall, Hamil; Silver, Jonathan (Bristol University Press, 2023)
EPDF and EPUB available Open Access under CC-BY-NC-ND licence. Focusing on material and social forms of infrastructure, this edited collection draws on rich empirical details from cities across the global North and South. The book asks the reader to think through the different ways in which infrastructure comes to be present in cities and its co-constitutive relationships with urban inhabitants and wider processes of urbanization. Considering the climate emergency, economic transformation, public health crises and racialized inequality, the book argues that paying attention to infrastructures' past, present and future allows us to understand and respond to the current urban condition.